Facilitating participation in clinical trials during pregnancy. (6th February 2023) - Vousden, Nicola; Haynes, Richard; Findlay, Sarah; Horby, Peter; Landray, Martin; Chappell, Lucy; Knight, Marian
Abstract : Nicola Vousden and colleagues call for wider inclusion of pregnant women in clinical trials to increase access to safe and effective treatments and reduce inequity in outcomes